Awareness of maternal health services among micro health insurance beneficiaries - Hoque, Mohima Benojir (International Journal Of Community Medicine And Public Health, 2017)
Background: Micro insurance for health is one method to address unmet health needs. Women are the primary and target market for micro- insurance for health. The study was conducted to assess the level of awareness on maternal health services among the micro health insurance beneficiaries. Methods: This cross-sectional study was done on 230 micro health insurance beneficiaries and 223 non-insured. The beneficiaries belonged to SAJIDA Foundation under Keraniganj thana and the non- insured belonged to Basila under Mohammadpur thana of Dhaka district. Purposive sampling technique was employed to select the sample and data were collected by face to face interview using a structured interview schedule. Results: The mean age ± SD of the women were 28.1 years ± 5.7 and 24.8 years ± 4.9 in program and comparison area respectively. The mean family income of the respondents of program and comparison area were 14489.13 Tk ± 12641.17 and 6814.35 Tk ± 3010. The women of the program area were more aware about the different components of maternal health than that of comparison area. Majority (93.9%) of women in program area were fully aware of maternal health services than that of comparison area (55.6%). Statistically significant (P <0.001, c2 = 90.72, df = 2) association was found between micro health insurance and level of awareness. Conclusions: Study shows higher proportions of women in programme area were aware on different components of maternal health services than in comparison area. Based on the study findings it can be recommended that steps should be taken to further improvement of the level of awareness on the factors influencing maternal health and the comparison area needs special attention to improve maternal health.